Early-strength and shrinkage-reducing agent for ordinary portland cement, its preparation method and application

By adding boric acid and calcium sulfate whiskers in the amorphous tricalcium aluminate grinding process and combining bismuth oxide catalyst, the problems of low early strength and large shrinkage of ordinary silicate cement are solved, and the application of building materials with high early strength, stable later strength and stable volume are achieved.

CN119638251BActive Publication Date: 2025-07-04BEIJING UNIV OF TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510040056.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-07-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing ordinary silicate cement has problems such as slow hydration rate, long settling time, low early strength and large shrinkage rate, which limits its application in the field of construction engineering, especially in the fields of coal mine blocking, tunnel jetting, road emergency repair and waterproof leakage blocking.

Method used

In the amorphous tricalcium aluminate grinding process, the appropriate amount of boric acid and calcium sulfate whiskers were added, and the catalyst was prepared by extracting bismuth oxide from tungsten tailings sand particles. By accurately regulating the hydration process, the network structure of AFt crystals and C-S-H gel was generated, which increased early strength and reduced shrinkage.

Benefits of technology

It has achieved high early strength, stable growth in later strength, low shrinkage rate and good volume stability, and is suitable for building materials applications under wet conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of admixtures for cement-based building materials, and in particular to an early-strength and shrinkage-reducing agent for ordinary portland cement, its preparation method and application. In the grinding process of amorphous tricalcium aluminate, an appropriate amount of boric acid is added, and calcium sulfate whiskers are added to precisely control the hydration process, improve the early strength of ordinary portland cement, reduce shrinkage, and further extract bismuth oxide from tungsten tailings sand particles and prepare a catalyst in combination with yttrium oxide to further improve the early shrinkage-reducing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of admixtures for cement-based building materials, and particularly to an early-strength and shrinkage-reducing agent for ordinary Portland cement, its preparation method and application. Background Art

[0002] Ordinary Portland cement, as a common hydraulic cementitious material, has the advantages of high late strength and good durability, and is thus widely used in the construction building materials industry. However, it also has the disadvantages of slow hydration rate, long setting time, low early strength, and large shrinkage rate; in the actual use process, it restricts the development and application in the field of construction engineering, especially in fields such as coal mine plugging, tunnel spraying, road emergency repair, waterproof plugging, and airport maintenance, which require rapid setting, early strength, and outstanding low shrinkage and high crack resistance performance, and is severely restricted. For a long time in the above fields of inorganic cementitious materials, we generally use the following types of cement: 1. Ordinary cement compounded with aluminate (calcium sulfoaluminate) cement. 2. Ordinary cement compounded with aluminate (or calcium sulfoaluminate) cement and gypsum. 3. Ordinary cement compounded with a quick-setting agent and a crystal nucleus early-strength agent. 4. Ordinary cement compounded with calcium aluminate powder (plus gypsum). However, the current ordinary cement composite systems all have disadvantages to varying degrees.

[0003] 1. Ordinary cement compounded with aluminate (calcium sulfoaluminate) cement accelerates the setting and hardening time of ordinary cement and improves the early strength of the composite system by using the quick-hardening characteristics of aluminate (calcium sulfoaluminate) according to the composite ratio of the two different cements. Patent ZL201610221606.7. However, the composite ratio is generally 20% - 60%, the dosage is relatively large, and there are special requirements for the variety and process of the composite admixture, and the control difficulty is large, and the late strength is prone to reverse shrinkage. 2. Ordinary cement compounded with aluminate (or calcium sulfoaluminate) cement and gypsum, on the basis of the two composite cements, adds gypsum to adjust its setting time, shrinkage rate and late strength. Patent ZL201610103518.7. Although it reduces the dry shrinkage rate in the air to a certain extent, the later expansion rate is relatively high (in water), the expansion stabilization period becomes longer, which is not conducive to application under humid conditions. At the same time, the dosage in the cement system is generally still 20% - 50%, and the dosage is relatively high. 3. Ordinary cement compounded with a quick-setting agent and an early-strength agent adds quick-setting agents and early-strength agents such as sodium metaaluminate, sodium aluminate, aluminum sulfate, sodium fluoride, sodium sulfate, sodium carbonate, calcium formate, etc. to ordinary cement to catalyze the early strength of ordinary Portland cement. ZL202411200082.4. However, although such a system has a fast setting and hardening speed, it does not have high early strength, and the various added admixtures will exacerbate the shrinkage rate of ordinary cement.

[0004] Patent ZL202211211091.4: The crystal nucleus type early strength agent can improve the strength after 1-day age, but it is not obvious for early improvement, and there is no comparison data on the shrinkage deformation amount either. 4. Ordinary cement compounded with calcium aluminate powder (plus gypsum): Adding calcium aluminate to ordinary cement will accelerate the setting, but it cannot provide very high early strength; with the addition of gypsum, the setting time will be extended, but when the dosage is generally low, the early strength effect is not obvious. When the dosage is large, the strength at 4 hours can be increased. At the same time, the shrinkage deformation amount of this system has no obvious improvement compared with ordinary cement (Patent ZL201510502127.8).

[0005] Therefore, how to use ordinary Portland cement as the basis and add appropriate modified admixtures to achieve a composite cementitious material system with low dosage, good early strength, low shrinkage, and stable expansion can not only solve the practical problems in the existing engineering field, but also has good social value and economic value for the healthy development of the building materials field. Summary of the Invention

[0006] To solve the problems existing in the prior art, the present invention provides an early strength and shrinkage reducing agent for ordinary Portland cement. Specifically, in the present invention, an appropriate amount of boric acid is added during the grinding process of amorphous tricalcium aluminate, and calcium sulfate whiskers are added to precisely control the hydration process, improve the early strength of ordinary Portland cement, reduce shrinkage, and further extract bismuth oxide from tungsten tailings sand particles and prepare a catalyst in combination with yttrium oxide to further improve the early shrinkage reduction effect.

[0007] Specifically, the preparation method of the early strength and shrinkage reducing agent for ordinary Portland cement of the present invention includes the following steps:

[0008] 1) Mix amorphous tricalcium aluminate and boric acid in a mass ratio of 100:(0.4 - 0.6) and ball mill to 700 - 800 m 2 / kg to obtain a modified masterbatch.

[0009] 2) Mix the modified masterbatch and calcium sulfate whiskers evenly in a mass ratio of N:(10 - N), where N = 6 - 8, to obtain the product.

[0010] Preferably, the temperature during the ball milling process in step 1) is 100 - 170 °C.

[0011] In the present invention, boric acid is added during the grinding process of amorphous tricalcium aluminate. Since amorphous tricalcium aluminate has a relatively high hardness and needs to be ground to a relatively high fineness, the temperature of the ball mill during the grinding process is generally 100 - 170 °C. The added boric acid gradually decomposes to produce BO3 during the high-temperature ball milling process. 3- and Ca migrating in 3CaO•Al2O3 2+The reaction occurs to form calcium borate Ca3(BO3)2. Since calcium borate will adhere to the surface of amorphous calcium aluminate and has the property of being slightly soluble in water, the hydration reaction is thus delayed.

[0012] When the amount of boric acid is insufficient, the formed calcium borate coating film is too weak. Tricalcium aluminate in amorphous form reacts with water rapidly to form calcium aluminate hydrate C3AH6, causing the cement paste to set and harden quickly. However, as the hydration progresses, due to its stacked morphology and loose structure, the later strength decreases. When the amount of boric acid is large, the thickness of the formed calcium borate coating film is too large, and it is difficult for water molecules to pass through in a short time, resulting in an overly long setting time and a decrease in early strength. Adding an appropriate amount of boric acid to form a reasonable amount of calcium borate allows the calcium sulfate whiskers to have sufficient time to react with tricalcium aluminate in amorphous form to form tiny AFt crystals during the early stage of hydration. The continuously generated AFt crystals fill the internal pores of the cement stone, making the structure more dense. The hydration products of ordinary Portland cement form a cross-linked network structure of C-S-H gel and AFt, which are firmly and tightly combined, so the early strength is high and the later strength continues to increase steadily. Due to complete and sufficient hydration, reasonable hydration process and hydration space, and reasonable size and quantity of C-S-H gel and AFt crystals, the shrinkage rate in dry air is low, the expansion stable period is short, and the expansion rate in water is not high.

[0013] The AFt crystals formed by tricalcium aluminate in amorphous form with a reasonable fineness and calcium sulfate whiskers become smaller in size, more evenly distributed, and more tightly packed. However, when the fineness is too fine, the specific surface area increases, and calcium borate cannot effectively coat the surface of the particles continuously, resulting in "quick setting"; when the specific surface area is too low, the reaction time is significantly longer. However, after the fineness becomes coarser, the activity of the material becomes lower, and the reaction degree is greatly reduced, so the best strength index cannot be achieved.

[0014] Preferably, in step 1), the mass ratio of tricalcium aluminate in amorphous form to boric acid is 100:0.5.

[0015] Preferably, in step 1), mix and ball mill to 750m 2 / kg.

[0016] Preferably, in step 2), the mass ratio of the modified masterbatch to calcium sulfate whiskers is 7:3.

[0017] In the present invention, through experiments for comparison, tricalcium aluminate in amorphous form and boric acid are mixed and ball milled to 700 - 800m 2 / kg according to the mass ratio of 100:(0.4 - 0.6) to obtain the modified masterbatch. The modified masterbatch and calcium sulfate whiskers are mixed evenly at a mass ratio of N:(10 - N). The effect is more ideal when N = 6 - 8. Especially when the mass ratio of tricalcium aluminate in amorphous form to boric acid is 100:0.5 and mixed and ball milled to 750m 2 / kg, the best effect is achieved when the mass ratio of the modified masterbatch to the calcium sulfate whisker is 7:3. This is because the quantity and size of the AFt crystals generated by the reaction of the composite cementitious material system are reasonably matched with the quantity of the C-S-H gel. At this time, the comprehensive strength development is the most ideal.

[0018] Regarding its mechanism, in the three different cases of insufficient, appropriate, and excessive boric acid addition amounts, the chemical reactions are as follows:

[0019] (1)Ca3Al2O6 + 6H2O = 3Ca(OH)2 + 2Al(OH)3

[0020] (2)3Ca(OH)2 + Ca3Al2O6 = 3CaO•Al2O3•6H2O (tricalcium aluminate hexahydrate C3AH6)

[0021] (3)CaSO4 + H2O = CaSO4•2H2O

[0022] (4)3CaO•Al2O3•6H2O + 3(CaSO4•2H2O) + 19H2O = 3CaO•Al2O3•3CaSO4•32H2O (ettringite AFt)

[0023] When the amount of Ca3(BO3)2 produced is insufficient and the formed coating layer is weak, water molecules quickly react with CA3, as shown in equations (1) and (2). The tricalcium aluminate hexahydrate C3AH6 produced will cause the composite cementitious material to quickly set, without time to react with the nano calcium sulfate whiskers. Therefore, the early formed skeleton is relatively thick, the crystal size is large, the strength development is very poor, the structure is not dense, and the shrinkage deformation amount is relatively high. When the amount of Ca3(BO3)2 produced is appropriate and matches the hydration reaction rate, when water molecules enter, there is sufficient time to react with the nano calcium sulfate whiskers. There are consecutive reactions of (1), (2), (3), and (4), and the final hydration product is ettringite AFt. During this process, the material reaction process matches the hydration rate, the crystal size of the formed ettringite AFt is reasonable, and it is fully wrapped together with the C-S-H hydrated calcium silicate gel and part of the aluminosilicate gel formed by the hydration of ordinary Portland cement. Therefore, the setting time is appropriate, the early and late strengths are relatively high, and the size deformation amount is the smallest. When the amount of Ca3(BO3)2 produced is excessive, the surface covering film layer is too thick, and it needs to be continuously dissolved as water molecules enter, and the hydration rate is too slow. Therefore, the setting time is relatively long, and the early and late strengths are relatively low.

[0024] Preferably, in step 2), the calcium sulfate whisker has a diameter of 1.5 - 2 μm and a length of 200 - 220 μm.

[0025] Preferably, the preparation method of the early strength and shrinkage reducing agent for ordinary Portland cement of the present invention further includes the following steps:

[0026] 3) Mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid, and water in a mass ratio of 100:(0.5 - 1):(0.1 - 0.2):100.

[0027] 4) Remove the tungsten tailings sand particles, use cation exchange resin to remove the impurity ions in the mixed solution, calcine the residue at 700 - 750 °C to obtain bismuth oxide, and mix bismuth oxide and yttrium oxide in a mass ratio of 6:4 to obtain a catalytic promoter.

[0028] 5) Mix the mixture of modified masterbatch and calcium sulfate whiskers and the catalytic promoter in a mass ratio of 10:(0.2 - 0.6), and mix evenly to obtain the product.

[0029] Furthermore, the present invention extracts high-purity bismuth oxide from solid waste tungsten tailings sand particles, mixes it with yttrium oxide to prepare a catalytic promoter, and further improves the performance of the early strength and shrinkage reducing agent. The present invention makes a reasoning explanation for its mechanism. Using tributyl phosphate as an extractant and phosphoric acid as a regulator, the ions generated by bismuth oxide in tungsten tailings sand particles (Bi 3+ ) interact with the phosphate ions (PO4 3- ) ionized from phosphoric acid to form a [Bi(PO4)] complex. Bismuth element dissolves out from the solid structure of tungsten tailings. Phosphoric acid accelerates the extraction of bismuth by tributyl phosphate (TBP). After removing the tungsten tailings sand particles, use cation exchange resin to remove impurity ions such as calcium, magnesium, and iron in the solution, and then perform high-temperature calcination to obtain high-purity bismuth oxide, which is mixed with yttrium oxide to prepare a catalytic promoter. During the use of the composite catalyst formed by the above method, it cooperates with the reaction of the modified masterbatch and calcium sulfate whiskers, and optimizes the crystal composition, colloid growth structure, and hydration reaction rate of the composite cementitious material system composed of ordinary Portland cement and the early strength and shrinkage reducing agent, further improving the ductility and compactness of the cement-based material, reducing the shrinkage rate further, and increasing the strength further.

[0030] Preferably, the calcination time in step 4) is 4 - 5 h.

[0031] Preferably, the mass ratio of the mixture of modified masterbatch and calcium sulfate whiskers to the catalytic promoter in step 5) is 10:(0.3 - 0.5).

[0032] More preferably, the mass ratio of the mixture of modified masterbatch and calcium sulfate whiskers to the catalytic promoter in step 5) is 10:0.4.

[0033] The present invention also relates to an early strength and shrinkage reducing agent for ordinary Portland cement, specifically, it is prepared by the above preparation method.

[0034] The present invention also relates to the application of the above early strength and shrinkage reducing agent in cement-based building materials.

[0035] Preferably, the addition amount of the early-strength shrinkage-reducing agent is 5-8% of the mass of ordinary Portland cement.

[0036] The present invention has the following technical advantages:

[0037] 1. The present invention modifies the amorphous tricalcium aluminate in grinding by using boric acid to generate a calcium borate coating with an appropriate thickness, and reasonably controls the specific surface area and the content of calcium sulfate whiskers after grinding, so as to prepare an early-strength shrinkage-reducing agent with improved early strength and volume stability of ordinary Portland cement.

[0038] 2. The present invention extracts bismuth oxide from solid waste tungsten tailings sand particles and mixes it with yttrium oxide to prepare a catalytic aid, which can further promote the effect of the early-strength shrinkage-reducing agent.

[0039] 3. The early-strength shrinkage-reducing agent prepared by the present invention can adjust the number and size of AFt crystals and the amount of C-S-H gel generated by the reaction of the composite cementitious material system, improve the ductility and compactness of the cement-based material, further reduce the shrinkage rate, and further increase the strength. Specific embodiments

[0040] To characterize the technical effects of the present invention, an early-strength shrinkage-reducing agent was prepared and its performance was tested. During the test, P·O42.5 cement produced by Tangshan Jidong Co., Ltd. was used, and its indicators met the requirements of GB175. The amorphous calcium aluminate powder was produced by Henan Hecheng Inorganic Materials Co., Ltd. The calcium sulfate whiskers had a diameter of 1.5-2 μm and a length of 200-220 μm, and were produced by Sichuan Jingying New Materials Technology Co., Ltd. The anhydrous gypsum powder had a specific surface area of 500 m 2 / kg, the sand was 20-70 mesh washed and dried river sand, the shrinkage-reducing agent was a polycarboxylate water-reducing agent of model PC-100 produced by Shanghai Yingshan Co., Ltd., and the defoaming agent was a mineral oil defoaming agent of model P803 produced by German Mingling Co., Ltd.

[0041] Example 1: This example was to verify the mass ratio of amorphous tricalcium aluminate to boric acid and the ball milling fineness, and a cement paste was used for the test. The cement paste formula was 100 parts of cement, 7 parts of the early-strength shrinkage-reducing agent, and 40 parts of water. The preparation method of the early-strength shrinkage-reducing agent included the following steps: 1) Mix and ball mill amorphous tricalcium aluminate and boric acid to obtain a modified masterbatch; 2) Mix the modified masterbatch and calcium sulfate whiskers evenly according to a mass ratio of 7:3 to obtain the product.

[0042] Example 1-1: In step 1), amorphous tricalcium aluminate and boric acid were mixed at a mass ratio of 100:0.5 and ball milled to 750 m 2 / kg.

[0043] After testing, the workable time of the cement paste was 185 s, the 1 h compressive strength was 10.8 MPa, and the 1 h flexural strength was 3.7 MPa.

[0044] Example 1-2: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.3 and ball-milled to 750 m 2 / kg.

[0045] After testing, the workable time of the neat paste is 45 s, the 1-hour compressive strength is 0.7 MPa, and the 1-hour flexural strength is 0.2 MPa.

[0046] Example 1-3: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.7 and ball-milled to 750 m 2 / kg.

[0047] After testing, the workable time of the neat paste is 460 s, the 1-hour compressive strength is 3.8 MPa, and the 1-hour flexural strength is 0.6 MPa.

[0048] Example 1-4: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.5 and ball-milled to 650 m 2 / kg.

[0049] After testing, the workable time of the neat paste is 455 s, the 1-hour compressive strength is 3.2 MPa, and the 1-hour flexural strength is 1.1 MPa.

[0050] Example 1-5: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.5 and ball-milled to 850 m 2 / kg.

[0051] After testing, the workable time of the neat paste is 25 s, the 1-hour compressive strength is 4.5 MPa, and the 1-hour flexural strength is 1.4 MPa.

[0052] Example 1-6: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.3 and ball-milled to 650 m 2 / kg.

[0053] After testing, the workable time of the neat paste is 1450 s, the 1-hour compressive strength is 0 MPa, and the 1-hour flexural strength is 0 MPa.

[0054] It can be seen from the test results that the boric acid content and the specific surface area of the modified masterbatch have a great influence on the workable time and early strength.

[0055] Example 2: In this example, to verify the influence of the raw material addition method, mortar was used for the test. The mortar formula is 100 parts of cement, 7 parts of early strength and shrinkage reducing agent, 50 parts of sand, 0.2 parts of water reducing agent, 0.05 parts of defoaming agent, and the water-cement ratio is 0.2.

[0056] Example 2-1: The early strength and shrinkage reducing agent was prepared by the method used in Example 1-1.

[0057] After testing, the workable time of the mortar is 15 min, the compressive / flexural strength at 1 h is 15.0 MPa / 3.9 MPa, the compressive / flexural strength at 4 h is 28.5 MPa / 5.7 MPa, the compressive / flexural strength at 1 d is 57.8 MPa / 9.2 MPa, the compressive / flexural strength at 3 d is 93.7 MPa / 11.9 MPa, the compressive / flexural strength at 28 d is 125.0 MPa / 14.8 MPa, the dimensional change rate in dry air at 28 d is -0.018%, and the dimensional change rate in water at 28 d is +0.021%.

[0058] Example 2-2: Early-strength and shrinkage-reducing agent. The preparation method includes the following steps: 1) Ball-mill amorphous tricalcium aluminate to 750 m 2 / kg, and then mix it with boric acid in a mass ratio of 100:0.5 to obtain a modified masterbatch. 2) Mix the modified masterbatch and calcium sulfate whiskers evenly in a mass ratio of 7:3 to obtain the product.

[0059] After testing, the workable time of the mortar is 32 min, the compressive / flexural strength at 1 h is 2.7 MPa / 0.9 MPa, the compressive / flexural strength at 4 h is 5.9 MPa / 3.5 MPa, the compressive / flexural strength at 1 d is 38.5 MPa / 6.4 MPa, the compressive / flexural strength at 3 d is 82.7 MPa / 9.3 MPa, the compressive / flexural strength at 28 d is 110.5 MPa / 13.6 MPa, the dimensional change rate in dry air at 28 d is -0.14%, and the dimensional change rate in water at 28 d is +0.38%.

[0060] Example 2-3: Early-strength and shrinkage-reducing agent. The preparation method includes the following steps: 1) Ball-mill amorphous tricalcium aluminate to 750 m 2 / kg, and then mix it with boric acid in a mass ratio of 100:0.5 to obtain a modified masterbatch. 2) Mix the modified masterbatch and anhydrous gypsum powder evenly in a mass ratio of 7:3 to obtain the product.

[0061] After testing, the workable time of the mortar is 8 min, the compressive / flexural strength at 1 h is 0 MPa / 0 MPa, the compressive / flexural strength at 4 h is 0 MPa / 0 MPa, the compressive / flexural strength at 1 d is 29.7 MPa / 5.1 MPa, the compressive / flexural strength at 3 d is 67.4 MPa / 7.8 MPa, the compressive / flexural strength at 28 d is 89.9 MPa / 10.2 MPa, the dimensional change rate in dry air at 28 d is -0.26%, and the dimensional change rate in water at 28 d is +0.49%.

[0062] From the test results, it can be seen that the raw material addition method will affect the workable time and mechanical properties of the mortar, and significantly affect the dimensional change rates in dry air and water. The dimensional change rates in dry air and water in Example 2-2 and Example 2-3 increase significantly, and the volume stability is poor.

[0063] Example 3: This example verifies the influence of the addition of a catalytic promoter on the properties of mortar. The mortar formula is 100 parts of cement, 7.35 parts of an early-strength and shrinkage-reducing agent, 50 parts of sand, 0.2 parts of a water-reducing agent, 0.05 parts of an antifoaming agent, and the water-to-material ratio is 0.2.

[0064] The early-strength and shrinkage-reducing agent, the preparation method of which includes the following steps: 1) Mix amorphous tricalcium aluminate and boric acid in a mass ratio of 100:0.5 and ball-mill to 750m 2 / kg to obtain a modified masterbatch; 2) Mix the modified masterbatch and calcium sulfate whiskers evenly in a mass ratio of 7:3 to obtain a mixture of the modified masterbatch and calcium sulfate whiskers; 3) Mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid, and water in a mass ratio of 100:0.7:0.1:100; 4) Remove the tungsten tailings sand particles, use cation exchange resin to remove the impurity ions in the mixed solution, and calcine the remaining material at 730°C for 4h to obtain bismuth oxide. Mix bismuth oxide and yttrium oxide in a mass ratio of 6:4 to obtain a catalytic promoter; 5) Mix the mixture of the modified masterbatch and calcium sulfate whiskers and the catalytic promoter evenly in a mass ratio of 10:0.5 to obtain the product.

[0065] After testing, the workable time of the mortar is 10 min, the 1h compressive / flexural strength is 16.9 MPa / 5.2 MPa, the 4h compressive / flexural strength is 36.7 MPa / 6.3 MPa, the 1d compressive / flexural strength is 66.9 MPa / 10.8 MPa, the 3d compressive / flexural strength is 107.2 MPa / 13.2 MPa, the 28d compressive / flexural strength is 133.7 MPa / 16.0 MPa, the 28d dry air dimensional change rate is -0.017%, and the 28d water dimensional change rate is +0.015%.

[0066] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A preparation method of an early strength and shrinkage reducing agent for ordinary Portland cement, characterized in that, It includes the following steps: 1) Mix amorphous tricalcium aluminate and boric acid in a mass ratio of 100:(0.4 - 0.6) and ball mill to 700 - 800 m 2 / kg to obtain a modified masterbatch, 2) Mix the modified masterbatch and calcium sulfate whiskers evenly according to the mass ratio of N:(10 - N), where N = 6 - 8, and that's it.

2. The preparation method according to claim 1, characterized in that, In step 1), the mass ratio of amorphous tricalcium aluminate to boric acid is 100:0.

5.

3. The preparation method according to claim 1, wherein Step 1) Mix and ball mill to 750 m 2 / kg.

4. The preparation method according to claim 1, characterized in that, In step 2), the mass ratio of the modified masterbatch to calcium sulfate whiskers is 7:

3.

5. The preparation method according to claim 1, characterized in that, In step 2), the diameter of the calcium sulfate whiskers is 1.5 - 2 μm, and the length is 200 - 220 μm.

6. The preparation method according to claim 1, wherein It also includes the following steps: 3) Mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid, and water according to the mass ratio of 100:(0.5 - 1):(0.1 - 0.2):

100. 4) Remove the tungsten tailings sand particles, use cation exchange resin to remove the impurity ions in the mixed solution, calcine the residue at 700 - 750 °C to obtain bismuth oxide, and mix bismuth oxide and yttrium oxide according to the mass ratio of 6:4 to obtain the catalytic assistant. 5) Mix the mixture of the modified masterbatch and calcium sulfate whiskers and the catalytic assistant evenly according to the mass ratio of 10:(0.2 - 0.6), and that's it.

7. The preparation method according to claim 1, characterized in that, In step 5), the mass ratio of the mixture of the modified masterbatch and calcium sulfate whiskers to the catalytic assistant is 10:(0.3 - 0.5).

8. An early strength and shrinkage reducing agent for ordinary portland cement, characterized in that, Prepared by the preparation method described in any one of claims 1 - 7.

9. The application of the early - strength and shrinkage - reducing agent according to claim 8 in cement - based building materials.

10. The application according to claim 9, characterized in that, The addition amount of the early - strength and shrinkage - reducing agent is 5 - 8% of the mass of ordinary Portland cement.

Citation Information

Patent Citations

  • A cement early strength agent and its preparation method

    CN105084799B

  • Super-high early-strength cement foundation grouting material

    CN105801060A

  • A sulfoaluminate-Portland cement composite system admixture, rapid hardening early strength concrete and preparation method thereof

    CN105884239B

  • A nanocrystalline nucleus-type early-strength cement grinding aid and its preparation method

    CN115368052B

  • Early hardening concrete and production method thereof

    CN118908640A